Self-Reported Dental Health Perception, its Consequences and Utilization of Oral Health Services among School Going Adolescent Girls in a Selective School of Dhaka Mohanagar: A Cross-Sectional Study (Journal of Dentistry and Allied Science, 2025)
Background: Oral health is an essential part of overall health and quality of life. The aim of the study was to assess the self-reported perception of dental condition, its consequences and utilization of oral health services among school girls in a selective secondary school of Dhaka Mohanagar. Methods: This cross-sectional study was carried out among 155 adolescents’ girls aged between 15 to 18 years at Siddheswari Girls’ High School, Dhaka in December 2023 using a convenient sampling method. After obtaining informed written consent from participants, data were collected through face-to-face interview using a pretested semi-structured questionnaire (Bengali language) regarding sociodemographic characteristics, self-perception of dental health condition & its consequences and utilization of oral health services. Collected data were edited and analyzed using IBM Statistical Package for the Social Sciences (SPSS) software version 27. Descriptive statistics presented by frequency, percentages, mean, standard deviation and bivariate analysis was done by Chi-square test (level of significance